The role of childhood maltreatment, current stress, and alexithymia in nonsuicidal self-injury: A sex-specific analysis among Korean young adults - Eunjin Jo; Gyumyoung Kim; Ji-Won Hur (PLoS ONE, 2026)
Prior research has highlighted various risk factors for nonsuicidal self-injury (NSSI), yet inconsistencies remain regarding their predictive value and sex-specific effects. This study examined how childhood maltreatment, current perceived stress, and alexithymia contribute to the engagement and severity of NSSI, with a focus on sex differences. A total of 731 individuals participated in this study (233 males, 498 females). The sample consisted of 481 individuals with NSSI (124 males, 357 females) and 250 control participants without a history of NSSI (109 males, 141 females). Logistic and multiple regression analyses were conducted separately by sex to test the differential predictive value of the factors. Among males, physical abuse significantly predicted NSSI engagement, and current stress was uniquely linked to greater NSSI method versatility. Conversely, in females, emotional abuse, current stress, and alexithymia emerged as key predictors of NSSI engagement, while sexual abuse, physical neglect, and alexithymia predicted greater severity. These findings underscore the existence of distinct, sex-specific pathways linking early adversity, emotional processing difficulties, and proximal stress to both the engagement and severity of NSSI. Tailoring prevention and intervention strategies to account for these sex-specific patterns is required to improve clinical outcomes.